Leading knowledge mobilization for public value: The case of the congestion charge zone (Area C) in Milan - Trivellato, Benedetta et al (Public Administration)
The literature on public value creation has grown significantly in recent years. However, how such generation of public value is linked to the interaction between individual and organizational capabilities, and the role played by leadership in such interaction, is still underexplored. This analysis of the congestion charge zone (Area C) implemented by the Municipality of Milan in Italy explores this issue and highlights the role played by the knowledge orchestrator who, by assuming different leadership roles at different times, strives to create value through knowledge mobilization. Leveraging from existing resources, the knowledge orchestrator captures knowledge from the external environment and promotes collaboration among individuals and institutions, so as to generate a new reconfigured stock of knowledge. These activities nurture the capacity of public organizations to collaborate, produce innovations, and more broadly contribute to public value creation. - Reproduced.
Keywords: Public administration; Network governance